Literature Review on Innovative Volleyball Learning Models in Physical Education - Awaluddin, Awaluddin; Hasanuddin, M. Imran (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This literature review explores recent developments in innovative volleyball learning models within physical education (PE), emphasizing student-centered strategies designed to improve technical skills, game understanding, motivation, and social interaction. A systematic review of 30 peer-reviewed national and Scopus-indexed journal articles published between 2014 and 2024 was conducted. The literature search utilized databases including Scopus, DOAJ, and Google Scholar, focusing on studies applying or evaluating instructional models such as Teaching Games for Understanding (TGfU), Sport Education Model (SEM), cooperative learning, and digital or multimedia-based methods. Findings reveal that the application of TGfU and SEM in volleyball PE led to significant improvements in students’ tactical knowledge and skill execution. For instance, a study by Munar et al. (2021) showed a 23.7% increase in cognitive decision-making scores after a 6-week SEM intervention. Additionally, Endriani et al. (2022) reported high feasibility in digital-based volleyball modules, with an effectiveness rating of 87.19% and learning practicality of 92.12%. Similarly, play-based and cooperative learning models demonstrated a positive impact on student motivation and participation (Padillah et al., 2020). Despite these advancements, gaps remain in longitudinal data, inclusivity across diverse student populations, and integration with online learning platforms. Therefore, future studies should focus on adaptive, hybrid, and gamified learning environments that promote equitable access and sustainable skill development in PE settings.